Elemental atmospheric deposition around North America’s largest metal processor of electronic waste (Horne Smelter, Canada) - Dupont, Jérémy; Ponton, Dominic E.; Marois, Arnaud; Fenton, Nicole J.; Amyot, Marc; Rosabal, Maikel (Frontiers in Environmental Chemistry, 2025)
The atmospheric deposition surrounding the Horne Smelter, a major metal processor of electronic wastes in North America has been studied primarily for metals historically associated with local mining operations, but not for other inorganic contaminants (e.g., rare earth elements, REEs) likely related to increasing recycling activities. To address this issue, the present work assessed the atmospheric deposition of a wide range of trace elements (TEs) using complementary monitoring approaches: passive air samplers (PAS) equipped with polyurethane foam (PUF), lichens (Cladonia rangiferina) and spiders (Lycosidae). Sampling was conducted in forest ecosystems (up to 24 sites) along a south-east transect spanning 52 km from the Horne Smelter. Metal concentrations in monitors consistently confirm the deposition of various TE (e.g., As, Cd, Cu, Hg, Pb) associated with the long-term mining activities in the region. Additionally, Hg and Ag were the only two TEs negatively correlated (p < 0.05) with lichen abundance, suggesting a toxic effect. A significant exponential decay regression was observed between TE concentration in the indicators with the distance from the smelter for most metals. Such findings indicated that the Horne Smelter is the main source of TE emission in the area. We also observed a clear enrichment in the first 30 km closest to the smelter compared to farther locations, where similar spatial gradient ranges of TE concentration were reported in the PAS (from 376 to 2) and in lichen (from 297 to 4). We measured, for the first time, levels of REEs and other metals (e.g., V, Mo) in the smelter-impacted area of Rouyn-Noranda. REE data showed no anomalies in their distribution across the sampled sites, suggesting that their source is probably not related to specific enrichment in recycled new technologies. Since the transect spatial results were similar for the PUF-PAS (short-term monitor) and the lichens (longer-term monitor), no significant changes in deposition patterns have occurred in recent years. Further, TEs in spiders were more variable, suggesting that ecological processes may alter this spatial pattern. This study highlights the importance of expanding biomonitoring efforts to include a broader variety of inorganic contaminants for smelter operations of electronic wastes around the world.